EEG-Microstates Reflect Auditory Distraction After Attentive Audiovisual Perception Recruitment of Cognitive Control Networks - Korn, Ute; Krylova, Marina; Heck, Kilian L.; Häußinger, Florian B.; Stark, Robert S.; Alizadeh, Sarah; Jamalabadi, Hamidreza; Walter, Martin; Galuske, Ralf A. W.; Munk, Matthias H. J. (Frontiers in Systems Neuroscience, 2021)
Processing of sensory information is embedded into ongoing neural processes which contribute to brain states. Electroencephalographic microstates are semi-stable short-lived power distributions which have been associated with subsystem activity such as auditory, visual and attention networks. Here we explore changes in electrical brain states in response to an audiovisual perception and memorization task under conditions of auditory distraction. We discovered changes in brain microstates reflecting a weakening of states representing activity of the auditory system and strengthening of salience networks, supporting the idea that salience networks are active after audiovisual encoding and during memorization to protect memories and concentrate on upcoming behavioural response.